Implementation of narcotics criminal law in Indonesia - Maria MT Manurung; Dzaki Jumayyil Pohan (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
The problem of narcotics crime has become a problem for nations and nations in the world that is always discussed. Throughout the world, the problem of narcotics abuse has almost become a problem for nations. And narcotics abuse can certainly cause physical damage, mental health, emotions and attitudes in society. The problem of narcotics abuse has threatened society and the nation so that it has become an organized crime in the national and international scope. Based on this background, the author raised a scientific journal entitled